A new superhard material C5N2 assembled from diamane: a first-principles study. (18th May 2023) - Shao, Jinfan; Qian, Yan; Kan, Erjun; Wu, Haiping
Abstract: Due to the shortage of diamond and cubic boron nitride (BN) and the lack of other potential rivals, searching for suitable superhard materials is still attracting tremendous research interests, especially those with special properties except for semiconducting and insulating characteristics. Beyond previous synthetic methods, here we give a new approach of designing superhard materials (i.e. stacking diamane layers through chemical adsorption of molecules at the interface) via first-principles calculations. As a result, a superhard carbon-rich C5 N2 compound with monoclinic C 2 symmetry is designed by inserting CN4 molecule between diamane layers, and it exhibits dynamical and mechanical stability at ambient environment. The hardness is estimated as 74.9 GPa, showing superhard nature. Different from indirect band gap insulators of diamond and cubic BN, C5 N2 behaves as a direct band gap semiconductor with an energy gap of ∼2.10 eV. Besides, the properties of C5 N2 can be effectively regulated by controlling the adsorbed molecules, for instance, it would turn into ferromagnetic phase with introduction of sp 3 hybridized three-folded C atoms and sp 2 hybridized two-fold coordinated N atoms. The estimated Curie temperatures of some ferromagnetic superhard phases are preferably above room temperature. Additionally, these ferromagnetic phases show diverse electronic properties, such as spin gapless semiconductor, bipolar magnetic semiconductor, metal, etc. This work opens a potential way to design superhard materials and tailor their physical properties, and can arouse their applications in spintronic field.